Legacies of forest harvesting on plant diversity and plant community composition in temperate deciduous forest. Issue 4 (18th November 2021) - Roy, Marie‐Ève; Surget‐Groba, Yann; Rivest, David
Abstract: Aims: To conserve forest natural heritage, sustainable forest harvesting requires the recovery of plant diversity and ecosystem functions following management. There is a need to clarify the temporal dynamics of plant diversity following harvesting, for both even‐aged and uneven‐aged silvicultural systems. To achieve this goal, the temporal dynamics of plant diversity in the herb layer were measured in unmanaged forests (control) and along a chronosequence (<5 years, 15 years and 30 years after harvesting) for even‐aged and uneven‐aged managed forests. Location: Hardwood forest of southern Quebec, Canada. Methods: Plant diversity, plant community composition and ecosystem functioning were investigated using metrics exploring richness, evenness and disparity diversity components, and included two scales of diversity partitioning (alpha and beta). Shrub–canopy layer, forest tree species composition and structure, and total forest basal area were also measured. Results: In both uneven‐aged and even‐aged managed forest stands, we found: (a) a substantial decrease in mean plant phylogenetic diversity compared with unmanaged forest, even 30 years after harvesting (i.e., decrease of 16% and 22%, respectively); and (b) lowest plant alpha‐diversity in the herb layer 15 years after harvesting. Modification of community composition based upon dissimilarity (beta‐diversity) metrics demonstrated more numerous effects of even‐aged management than uneven‐aged management. For forest composition and structure, plant community and plant traits, dissimilarity relative to the unmanaged control was highest 5 years after even‐aged management. Trait‐based communities were more similar to unmanaged forest at the intermediate levels of forest density (i.e., ~20 m 2 /ha) that were found 5 years after uneven‐aged management. Conclusions: Forest management clearly affected diversity, community composition and ecosystem functions along the chronosequence, highlighting the strongest effects of more intensive management (i.e., even‐aged) and the need to improve the sustainability of forest management. Abstract : We determined the effects of forest harvesting (clear cuts and partial harvests) on plant diversity 5, 15 and 30 years after harvesting, relative to unmanaged old‐growth forest. We found a substantial decrease in mean plant phylogenetic diversity (all periods after harvesting), plant alpha‐diversity (15 years after harvesting) and beta‐diversity of plant traits (5 years after clear‐cutting) in managed forests compared with unmanaged forest.